Predictors of Midwives' Anxiety During the COVID-19 Pandemic - Suhermawan Suhermawan; Asnawi Abdullah; Maidar Maidar; Marthoenis Marthoenis; Hafnidar A. Rani (Indonesian Journal of Global Health Research, 2024)
Midwives are healthcare workers who make the first physical contact with newborns during delivery. They bear significant responsibilities in preventing COVID-19, which can contribute to increased anxiety levels. Many factors are associated with healthcare workers' anxiety, yet studies specifically focusing on predictors of anxiety among midwives remain limited. This analytical study utilized a cross-sectional approach to identify predictors of anxiety among midwives during the COVID-19 pandemic in Nagan Raya District. The study involved a sample of 533 midwives, with data collected via Google Forms. Multivariate analysis was conducted using multiple logistic regression tests with a 95% confidence level. The study found that 43 midwives (81.24%) experienced anxiety during the COVID-19 pandemic. Factors significantly associated with anxiety included age ≥32 years (p-value = 0.006; OR = 1.86; 95% CI: 1.20–2.89), workload (p-value = 0.000; OR = 2.43; 95% CI: 1.53–3.84), independent midwifery practice (p-value = 0.044; OR = 4.44; 95% CI: 1.04–18.95), and acting as the primary birth attendant (p-value = 0.032; OR = 1.61; 95% CI: 1.04–2.49). The most dominant factor associated with anxiety was high workload (p-value = 0.000; OR = 2.35; 95% CI: 1.46–3.79). Midwives with high workloads were 2.35 times more likely to experience anxiety during the COVID-19 pandemic compared to those with lower workloads. It is recommended that midwives reduce their workloads and manage their tasks by creating structured work plans. Additionally, midwives should improve their managerial skills to distribute workloads effectively among team members.